2018
DOI: 10.1016/j.archoralbio.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal rhythm and salivary electrolyte

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Generally, overeating may be even more severe during quarantine due to extended stays at home with often unlimited access to food [32]. As shown in the present study, the increase in snacking may lead to a rise in the tendency to eat meals in the evening, which harms the oral cavity more than snacking during the day due to the inhibition of salivary secretion in the night rest [33]. This is significant mainly for population groups affected by hyposalivation, then typical dental complaints followed by an absence of salivary clearance may occur [34].…”
Section: Discussionsupporting
confidence: 48%
“…Generally, overeating may be even more severe during quarantine due to extended stays at home with often unlimited access to food [32]. As shown in the present study, the increase in snacking may lead to a rise in the tendency to eat meals in the evening, which harms the oral cavity more than snacking during the day due to the inhibition of salivary secretion in the night rest [33]. This is significant mainly for population groups affected by hyposalivation, then typical dental complaints followed by an absence of salivary clearance may occur [34].…”
Section: Discussionsupporting
confidence: 48%
“…These changes in the circadian profile of BP are also confirmed by a reduced percentage of the 24 h rhythm with the predominance of ultradian rhythms [4]. This profile of the circadian rhythm is characteristic of disorders of water-salt metabolism [48][49][50][51]. Analysis of ALI in this group revealed an increase in the number of patients with increased HR (over 80 bpm) in addition to the changes in CI.…”
Section: Discussionmentioning
confidence: 52%
“…and early colonization or high titer of Streptococci mutans in saliva [5]. Pyati et al (2018) found that the significant change in salivary flow rate, pH and total protein levels in active children with caries suggest that the levels of these physicochemical properties of saliva can act as strong indicators of caries status.…”
Section: Original Research Articlementioning
confidence: 99%
“…Xerostomia, also known as patient-reported subjective oral dryness, is a common side effect of cancer therapies, particularly radiation therapy in the head and neck region [1,2]. It influences the quality of life, counting oral infection, caries, poor sleep quality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%